Endogenous Ethanol and Triglyceride Production by Gut Pichia kudriavzevii, Candida albicans and Candida glabrata Yeasts in Non-Alcoholic Steatohepatitis - Babacar Mbaye; Patrick Borentain; Reham Magdy Wasfy; Maryam Tidjani Alou; Nicholas Armstrong; Giovanna Mottola; Line Meddeb; Stéphane Ranque; René Gérolami; Matthieu Million; Didier Raoult (Cells, 2022)
Nonalcoholic steatohepatitis (NASH) increases with fructose consumption and metabolic syndrome and has been recently linked with endogenous ethanol production, notably by high alcohol-producing Klebsiella pneumoniae (HiAlc Kpn). Candida yeasts are the main causes of auto-brewery syndromes but have been neglected in NASH. Here, the fecal ethanol and microbial content of 10 cases and 10 controls were compared. Ethanol was measured by gas chromatography-mass spectrometry. Species identification was performed by MALDI-TOF MS, and triglyceride production was assessed by a colorimetric enzymatic assay. The fecal ethanol concentration was four times higher in patients with NASH (median [interquartile range]: 0.13 [0.05–1.43] vs. 0.034 [0.008–0.57], p = 0.037). Yeasts were isolated from almost all cases but not from controls (9/10 vs. 0/10, p = 0.0001). Pichia kudriavzevii was the most frequent (four patients), while Candida glabrata, Candida albicans, and Galactomyces geotrichum were identified in two cases each. The concentration of ethanol produced by yeasts was 10 times higher than that produced by bacteria (median, 3.36 [0.49–5.60] vs. 0.32 [0.009–0.43], p = 0.0029). Using a 10% D-fructose restricted medium, we showed that NASH-associated yeasts transformed fructose in ethanol. Unexpectedly, yeasts isolated from NASH patients produced a substantial amount of triglycerides. Pichia kudriavzevii strains produced the maximal ethanol and triglyceride levels in vitro. Our preliminary human descriptive and in vitro experimental results suggest that yeasts have been neglected. In addition to K. pneumoniae, gut Pichia and Candida yeasts could be linked with NASH pathophysiology in a species- and strain-specific manner through fructose-dependent endogenous alcohol and triglyceride production.